Pengaruh Komitmen Organisasional Dan Etika Kerja Terhadap Kinerja Tenaga Pendidik: Studi Perbandingan Madrasah Aliyah Dan Sekolah Menengah Atas Kota Bengkulu - Novandri - Saputra; Slamet - Widodo; Praningrum - - (Student Journal of Business and Management, 2021)
The purpose of this study is first, to determine and analyze the effect of organizational commitment on the performance of teaching staff at Madrasah Aliyah and Senior High Schools in Bengkulu City. Second, to determine and analyze the effect of work ethics on the performance of educators at Madrasah Aliyah and Senior High Schools in Bengkulu City. Third, to determine and analyze the effect of organizational commitment and work ethics on the performance of educators at Madrasah Aliyah and Senior High Schools in Bengkulu City. Fourth, to find out and analyze the differences in the performance of teaching staff at Madrasah Aliyah and Menangah Atas Schools in Bengkulu City. This study uses a quantitative approach to answer the first, second and third problem formulations because the data used is in the form of numbers and the type of causal associative research, namely research used to determine the effect of cause and effect between the independent variable and the dependent variable. The formulation of the fourth problem in this study used a quantitative approach with the comparison method. Respondents of the study consisted of 269 people who were MA and SMA teachers in Bengkulu City. The data collection technique used a questionnaire with data analysis techniques using the F test, t test and difference test. The results of this study indicate that first, the effect of organizational commitment is significant on the performance of teaching staff at Madrasah Aliyah and Senior High Schools in Bengkulu City. Second, work ethics on the performance of educators at Madrasah Aliyah and Senior High Schools in Bengkulu City. Third, organizational commitment and work ethics together on the performance of educators at Madrasah Aliyah and Senior High Schools in Bengkulu City. Fourth, there is no difference in the performance of teaching staff at Madrasah Aliyah and Senior High Schools in Bengkulu City.Keywords: Organizational Commitment, Work Ethics, Teacher Performance